Public debt, child allowances and pension benefits with endogenous fertility - Masaya Yasuoka; Atsushi Miyake (Economics: The Open-Access, Open-Assessment E-Journal, 2013)
The public debt stock in some economically developed countries continues to increase because of a lack of tax revenues and the concomitant burdens of social security. Many of those countries suffer from lower birth rates and consequently, have fewer children. Child allowances might be an effective way to increase fertility, leading to higher future tax revenues through an increase in the number of younger people. In this paper, the authors examine whether or not child allowances reduce the public debt stock as a share of GDP in an economy with a pension system. As long as a non-negative debt policy is adopted in the long run, child allowances financed by bonds always increase the public debt stock as a share of GDP.
Keywords: G23; H55; J13; 330; public debt; endogenous fertility; child allowances; pension; Öffentliche Schulden; Familienleistungsausgleich; Fruchtbarkeit; Gesetzliche Rentenversicherung; Bevölkerungsökonomie; Theorie